Natural Killer Cells Lessons and Challenges - Zhang, Leisheng (IntechOpen, 2023)
Natural killer (NK) cells are immune cells that can eliminate pathogenic microorganisms, aging cells, and tumor cells. State-of-the-art renewal has indicated the feasibility of large-scale preparation of autogenous and allogeneic NK cells from a variety of sources including peripheral blood, umbilical cord blood, placental blood, NK cell lines, and even stem cells such as pluripotent stem cells and hematopoietic stem cells. In the meantime, a range of methodologies has been developed for ex vivo expansion and activation of NK cells such as monolayer culture, coculture with trophoblast cells, bioreactors, cytokine cocktails, and physicochemical irritation. NK cell-based cytotherapy has proven effective for a variety of hematologic malignancies and metastatic solid tumors. This book provides a comprehensive overview of NK cell-based cytotherapy for cancer treatment, immunosurveillance, and immunotherapy.